Penerapan Model Pembelajaran Kooperatif Tipe Quick on The Draw Terhadap Peningkatan Garis dan Sudut Pada Siswa Kelas VII SMPN Padang Mawalle - Nurlina Nurlina; Fatimah Fatimah; Febryanti Febryanti (Journal Peqguruang: Conference Series, 2021)
This research is a class action research (classroom action research) which aims to determine the improvement of students’ conceptual understanding using the quick on the draw type cooperative learning model in seventh grade students of SMPN Padang Mawalle, this research was carrid out in two cycles, the procedure of research work in each cycle took place in four stages: planning, implememtation, observation, and reflection. The subjects of this research were the seventh grade students of SMPN Padang Mawalle, totaling 31 students. The instruments used in the study consisted of : (1) the researcher’s implementation observation sheet (2) the student activity observation sheet and (3) the concept   understanding ability test. The observation sheet was analyzed qualitatively while the consept understanding ability tes was analyzed quantitatively using descriptive statistical analysis. Based on the results of qualitative data analysis on the observation sheet on the oplementation of the cooperative learning model of the quick on the draw type in the first cicle, 75% in the second cycle experienced an increase to 91,66%. Based on the results of qualitative data analysis on students activity observation sheets, obtained in the first cycle 87,71% an the second cycle obtained 94,73%. While the results of the analysis of the understanding of the concept test obtained classical completeness in the first cycle was only 25,80% and increased t 83,87% in the second cycle. Based on data analysis, it can be concluded that the application of the quick on the draw type of cooperative learning model has increased the understanding of the cocept of lines and angles in seventh grade students of SMPN Padang Mawalle